Hospital length of stay and its predictors among surgical patients at public hospitals in Addis Ababa, Ethiopia - Sifer, Samuel Dessu; Abdela, Abduselam Ahmed; Getachew, Milkiyas Solomon; Assefa, Redait Awoke; Abere, Abatalem Minlargeh (Frontiers in Surgery, 2025)
BackgroundReducing the length of hospital stay can significantly lower healthcare costs, minimize the risk of hospital-acquired infections and complications, and improve patient well-being. Accordingly, this study aimed to assess the length of hospital stay and its predictors among surgical patients at public hospitals in Addis Ababa, Ethiopia.MethodsA prospective cohort study was conducted among 394 surgical patients from August 1 and November 30, 2023. The length of hospital stay was analyzed using Kaplan–Meier survival curves, and group differences were assessed with the log-rank test. Variables with a p-value less than 0.05 in the multivariable Cox proportional hazards model were considered statistically significant predictors.ResultThe median length of hospital stay was 6 days (IQR 5, 6). Comorbidity (AHR: 3.32; 95% CI: 1.01, 10.85), infection (AHR: 3.14; 95% CI: 1.77, 12.72), weight loss (AHR: 1.62; 95% CI: 1.03, 2.56), change in dietary pattern (AHR: 1.52; 95% CI; 1.98, 2.35) and change in functional capacity (AHR: 1.53; 95% CI: 1.12, 2.13) were independent predictors of length of hospital stay.Conclusion and recommendationsOur findings indicate that prolonged hospitalization is often a consequence of delayed recovery from surgery, particularly among patients with complicating conditions such as comorbidities, infections, poor nutritional status, and limited functional capacity. These findings underscore the need for integrated preoperative assessments and targeted interventions to optimize patient conditions, enhance postoperative recovery, and reduce hospital stay duration in resource-limited settings.